APPLICATIONS OF CONSTRUCTION AN EOG TELEVISION CONTROL MODEL - Ching-Sung, Wang; Sheng, Vincent Hoong Yong; Cheng-Jai, Wang (International Journal of Research -GRANTHAALAYAH, 2017)
Speaking and writing are two common easiest mediums of communication for human. However, they are not applicable when it comes to handicapped who has hearing or speaking inability. Handicapped often encounter a hard time in expressing their feelings and thoughts to others. Furthermore, there are abundant of product in the market, which uses eye movement, light reflection theory and electrooculogram (EOG) as the input of their control system. These implication aims to ease the disabled to use modern devices. Therefore, a research is done on constructing an EOG Television Control Model to help the disabled to have remote on the television. By using the eye’s electrical signal obtained via vertical and horizontal motion, user can easily control television by rolling or blinking their eyes. Motivation/Background: The main motivation for this research is to look for an alternative solution to help patients especially those with physical disabilities to control television using eyes motions without difficulties. Moreover, selection for the best television monitoring method among all possible solution is also one of the research progress. Method: The most important method being used in this research is by using EOG to detect eyes motion and convert each and every unique motion into a specific command for television monitoring action. Wireless communication device is an additional to allow long range television control using EOG signal. Results: It is shown that the EOG signal for left and right and up and down motion of eyeballs differ with each other. Using the motion and by setting a threshold value to quantized the signal, a better quality television monitoring command is generated. Conclusions: EOG signal allow user especially those with physical disabilities to monitor television with ease by performing unique eye rolling motion.